2007
DOI: 10.1021/es061575k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ambient NOx on Chlorophyll a Fluorescence in Transplanted Flavoparmelia caperata (Lichen)

Abstract: Transplants of Flavoparmelia caperata (L.) Hale were used to test possible relationships between chlorophyll a fluorescence (CaF) and ambient atmospheric conditions (temperature, precipitation, SO2 and NOx levels). Portions of the same thalli collected in a pristine site (A) of the Trieste Karst were exposed at that site, as the control, and in four other sites (B-E) in NE Italy, near to pollution monitoring stations. These sites had been selected in order to provide similar two by two climatic conditions (sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The measurement of modulated chlorophyll a, fluorescence in lichens is one of several valid tools in biomonitoring studies (Jensen and Kricke 2000;Tretiach et al 2007b). The chlorophyll fluorescence parameter ratio of variable fluorescence to maximal fluorescence (Fv/Fm) has been widely used to assess the state of the photosynthetic apparatus in response air pollution (Bjerke et al 2005;Fernandez-Salegui et al 2006a;Tretiach et al 2007a;Paoli et al 2010;Piccotto et al 2011;Karakoti et al 2014).…”
Section: Biomonitoring Methods With Lichensmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of modulated chlorophyll a, fluorescence in lichens is one of several valid tools in biomonitoring studies (Jensen and Kricke 2000;Tretiach et al 2007b). The chlorophyll fluorescence parameter ratio of variable fluorescence to maximal fluorescence (Fv/Fm) has been widely used to assess the state of the photosynthetic apparatus in response air pollution (Bjerke et al 2005;Fernandez-Salegui et al 2006a;Tretiach et al 2007a;Paoli et al 2010;Piccotto et al 2011;Karakoti et al 2014).…”
Section: Biomonitoring Methods With Lichensmentioning
confidence: 99%
“…The results of recent transplantation studies showed that the pulse amplitude modulation fluorimetry applied may become an important tool in biomonitoring studies. In such cases, particular care should be taken in sample collection, selection and exposure (Tretiach et al 2007b). …”
Section: Biomonitoring Methods With Lichensmentioning
confidence: 99%
See 1 more Smart Citation
“…However, air pollution impairs lichen colonization and survival (Barreno, 2002). SO 2 , O 3 and NO x have been related with lichen damage but the toxicity mechanisms overwhelming their extraordinary abiotic stress defence system have not been fully elucidated (Riddell et al, 2012(Riddell et al, , 2008Hauck et al, 2008;Tretiach et al, 2007;Kong et al, 1999;Ba ckor and Fahselt, 2003;Kong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These features of lichens, combined with their extraordinary capability to grow in a large geographical range and accumulate mineral elements far above their needs, rank them among the best bioindicators (Garty et al, 2003). The ability of lichens to tolerate and even bioaccumulate heavy metals such as As, Pb or Cd, has been extensively studied (Bajpai and Upreti, 2012;State et al, 2012;Ba ckor et al, 2011;Pawlik-Skowronska and Ba ckor, 2011;Ba ckor et al, 2010) as well as the noxious effects of inorganic pollutants such as O 3 , SO 2 or NO x (Riddell et al, 2012;Hauck et al, 2008;Tretiach et al, 2007;Hauck, 2010). However, the toxic effects of volatile organic pollutants (VOPs) on lichens have not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%